TINDAK TUTUR DALAM IKLAN LAYANAN MASYARAKAT DI KABUPATEN BANYUWANGI - Sasmita, Clara Ayu (Humanis; Volume 14. No.1. Januari 2016)
Speech act is actions through speech. Speech act can be found anywhere and occur at anytime during the process of communication. In this  research  use theory of pragmatics, there are speech act theory and speech act theory of functions. Methods and techniques used in this research consist of three, namely 1) “simak” method for data collection, 2) descriptive method for data analysis, and 3) informal method for presentation. Thus, the results obtained from this research are (1) types of speech act is a direct, indirect speech acts, and speech acts literal, and (2) functions of speech acts, that is declarative, representative, expressive, directive, and commissive.
Keywords: speech act, ILM, pragmatics